The Role of Islamic Economic Law in Strengthening Global Partnerships for Sustainable Development Goals - Amany, Amany; Janwari, Yadi; Hasanuddin, Muhammad; Sofiawati, Eva; Meinanti, Dwi Reiza (CV. Strata Persada Academia, 2025)
Islamic economic law is pivotal in strengthening global partnerships to achieve the Sustainable Development Goals (SDGs). Rooted in principles such as ethics, risk-sharing, and social justice, the Sharia-based economic system provides an inclusive and sustainable alternative to conventional economic frameworks. This study examines the contribution of Islamic economic law in fostering global partnerships and advancing SDGs, focusing on the role of Islamic financial instruments and the integration of technology in the Islamic finance sector. A qualitative approach was employed, utilizing literature reviews of relevant articles, case studies, and organizational reports on the role of Islamic economic law in global partnerships and SDG development. Data sources include prior research, international organization reports, and analyses of the Islamic economic sector. Findings reveal that Islamic economic law significantly addresses global economic inequalities through instruments such as zakat, waqf, and sukuk. The Islamic tourism sector also fosters local economic empowerment, while equity-based Islamic banking promotes socially and environmentally responsible investments. Technology integration in Islamic finance further enhances access to Sharia-compliant financial products and services, facilitating global partnerships and supporting sustainable economic growth.